2018
DOI: 10.1016/j.celrep.2018.02.084
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic IDH1 Mutations Promote Enhanced Proline Synthesis through PYCR1 to Support the Maintenance of Mitochondrial Redox Homeostasis

Abstract: SummarySince the discovery of mutations in isocitrate dehydrogenase 1 (IDH1) in gliomas and other tumors, significant efforts have been made to gain a deeper understanding of the consequences of this oncogenic mutation. One aspect of the neomorphic function of the IDH1 R132H enzyme that has received less attention is the perturbation of cellular redox homeostasis. Here, we describe a biosynthetic pathway exhibited by cells expressing mutant IDH1. By virtue of a change in cellular redox homeostasis, IDH1-mutate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(72 citation statements)
references
References 30 publications
1
71
0
Order By: Relevance
“…Finally, proline synthesis by pyrroline-5-carboxylate reductase (PYCR) from glutamine can also help regulate redox balance by regenerating NAD þ , which in turn may promote TCA cycling (34). Accordingly, we found that statin treatment robustly increased proline synthesis from glutamine ( Fig.…”
Section: Statin-induced Reduction In Coq Levels Causes Elevated Ros Amentioning
confidence: 77%
“…Finally, proline synthesis by pyrroline-5-carboxylate reductase (PYCR) from glutamine can also help regulate redox balance by regenerating NAD þ , which in turn may promote TCA cycling (34). Accordingly, we found that statin treatment robustly increased proline synthesis from glutamine ( Fig.…”
Section: Statin-induced Reduction In Coq Levels Causes Elevated Ros Amentioning
confidence: 77%
“…Proline metabolism in cancer cells has been recently recognised as a tumour vulnerability and potential target for therapy 70 . Cancer cells with low levels of proline synthesis enzymes or under nutrient limiting conditions are vulnerable to proline shortage 58,61 and proline synthesis is important to maintain mitochondrial redox homeostasis in cancer cells with IDH1 oncogenic mutations 71 .…”
Section: Discussionmentioning
confidence: 99%
“…c-Myc and PI3K upregulate proline synthesis [43]. Enhanced proline synthesis by PYCR, supporting mitochondrial redox homeostasis, was reported in an oligodendroglioma cell line with an IDH1 mutation [44]. Following synthesis, proline may be catabolized by the proline oxidase (proline dehydrogenase; POX/PRODH), a putative tumor suppressor.…”
Section: Glutamine Addiction In Gliomasmentioning
confidence: 92%